2009
DOI: 10.1099/jmm.0.007369-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diarrhoeagenic Escherichia coli in children from León, Nicaragua

Abstract: , a total of 526 faecal samples from children aged 0-60 months (381 with and 145 without diarrhoea) from Leó n, Nicaragua, were studied. In order to detect five different diarrhoeagenic Escherichia coli pathotypes simultaneously [enterotoxigenic E. coli (ETEC), enteroaggregative E. coli (EAEC), enteropathogenic E. coli (EPEC), enterohaemorrhagic E. coli (EHEC) and enteroinvasive E. coli (EIEC)], a mixture of eight primer pairs was used in a single PCR. At least one diarrhoeagenic E. coli pathotype was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
71
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 26 publications
(35 reference statements)
16
71
8
1
Order By: Relevance
“…ETEC was the dominant pathotype detected in children 6-12 months of age while EPEC was dominant in children 13-24 months of age in this study. The prevalence of EPEC in the 13-24 months age group conforms to the report that EPEC infection is primarily a disease of infants younger than two years of age [35]. The detection of atypical EPEC in Abuja, Nigeria, is in consonance with recent findings in developing and developed countries of increased isolation of atypical EPEC [37].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…ETEC was the dominant pathotype detected in children 6-12 months of age while EPEC was dominant in children 13-24 months of age in this study. The prevalence of EPEC in the 13-24 months age group conforms to the report that EPEC infection is primarily a disease of infants younger than two years of age [35]. The detection of atypical EPEC in Abuja, Nigeria, is in consonance with recent findings in developing and developed countries of increased isolation of atypical EPEC [37].…”
Section: Discussionsupporting
confidence: 67%
“…In Lagos, Nigeria, an earlier hospital-based study reported an established relationship between fever, vomiting, and hospitalization of diarrheic children [34]. Nonetheless, our data support the suggestion that infections with any of the diarrheagenic E.coli pathotypes are indistinguishable on the basis of clinical findings [35].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Positive E. coli cultures were assayed by multiplex PCR for the following pathotypes: enteropathogenic E.coli, enterotoxigenic E. coli, enteroaggregative E. coli, enteroinvasive E. coli, and enterohemorrhagic E. coli, as described by Vilchez. 15 Direct microscopy was used for detection of the parasitic enteropathogens, with concentration and acid-fast staining for the detection of Cryptosporidium spp., as described by Garcia. 16 16S rDNA amplicon sequencing and sequencing data analysis.…”
Section: Methodsmentioning
confidence: 99%